HARNESSING POLITICAL AND TRADE STRUCTURES TO ACHIEVE STANDARDS FOR EARTHEN BUILDING IN SOUTHERN AFRICA AND BEYOND - Keable, Rowland; Bakker, Karel Anthonie (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Following the adoption of the Code of Practice for Rammed Earth Structures by the Standards Association of Zimbabwe, it was decided to harmonize Standard by two regional blocs. Both COMESA (1) (19 countries) and SADC (2) (15 countries) agreed to do so but in practice, SADC was chosen to move the process forward. Four years on and the group is working with 10 of the 15 countries and have brought the process to the inal voting stage for harmonization. On acceptance, people in 15 countries will for the irst time be able to build earthen structures in urban areas under standards published by their own country. It seems that using the existing trade and political structures of regions is easier than single countries, and that earthen construction has to learn the language of international-trade agreements. It was decided to look at changing the restrictive building codes and building regulations through the language of global-standards systems; concepts such as Technical Barriers to Trade (TBT’s) may prove easier instruments to change than previous work with organizations already in the ield of construction and materials. However, this approach requires that members of states and of regions take up their position as stakeholders and use the existing apparatus to change the regulatory scenario, which has prevailed up till now. In this way, the acceptance of earth can be changed, as a useful economic tool, a viable construction material, a mean to increase employment and of reducing harmful greenhouse gases, from one of negative perceptions to one of positive adoption. Much of the groundwork has been laid out, not just by people working with earthen architecture but also by international institutions, such as the International Organization for Standards that needs to be engaged.